The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jhet.3648
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, Antifungal Activity, and Docking Study of Difluoromethyl Pyrazole Derivatives

Abstract: Nine novel difluoromethylpyrazole acyl urea derivatives were synthesized via seven steps conveniently. All the structures were determined by 1H‐NMR, 13C‐NMR, HRMS, and X‐ray diffraction. The in vivo fungicidal activities were determined against Corynespora mazei, Botrytis cinerea, Fusarium oxysporum, and Pseudomonas syringae, respectively. The bioassay results indicated that some of them displayed good control effective (around 50 and 80%) against P. syringae and B. cinerea at 50 mg/L, respectively, which is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…Recently, it has been shown that the antifungal activity of a variety of compounds is mainly due to inhibition of succinate dehydrogenase (SDH) which is a component of the mitochondrial respiratory chain and the tricarboxylic acid cycle [21][22][23]. Thus, the interactions of antifungal compounds with the ubiquinone binding site have been evaluated to understand the experimental activity shown by different series of related compounds [24][25][26][27][28]. In this work, we have performed molecular docking studies of geranylated phenols carrying one (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), two (34)(35)(36)(37)(38) or no (14, 18, 19) hydroxyl groups in the side alkyl chain.…”
Section: Molecular Docking Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, it has been shown that the antifungal activity of a variety of compounds is mainly due to inhibition of succinate dehydrogenase (SDH) which is a component of the mitochondrial respiratory chain and the tricarboxylic acid cycle [21][22][23]. Thus, the interactions of antifungal compounds with the ubiquinone binding site have been evaluated to understand the experimental activity shown by different series of related compounds [24][25][26][27][28]. In this work, we have performed molecular docking studies of geranylated phenols carrying one (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), two (34)(35)(36)(37)(38) or no (14, 18, 19) hydroxyl groups in the side alkyl chain.…”
Section: Molecular Docking Studymentioning
confidence: 99%
“…Thus, the interactions of antifungal compounds with the ubiquinone binding site have been evaluated to understand the experimental activity shown by different series of related compounds [24][25][26][27][28]. In this work, we have performed molecular docking studies of geranylated phenols carrying one (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), two (34)(35)(36)(37)(38) or no (14, 18, 19) hydroxyl groups in the side alkyl chain. Molecular coupling of these compounds to a single crystal structure of SDH (PDB code 2FBW) was carried out by using Glide software.…”
Section: Molecular Docking Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies 6,21,22 on HPPD inhibitors have proven that prodrug-type HPPD herbicides are an effective method of obtaining new HPPD inhibitors, such as the commercial HPPD herbicides benzobicyclon, isoxaflutole, benzofenap, pyrazolynate and pyrazoxyfen. As a part of our job in designing and synthesizing novel pyrazole derivatives with pesticidal activity, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] the pyrazole HPPD herbicides were used as lead compound, the 3-position of benzene ring was replaced by a flexible chain, and the hydroxyl group of pyrazole ring was also etherified or esterified. Through the prodrug strategy, we hoped that better herbicidal activity would result.…”
Section: Introductionmentioning
confidence: 99%